(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate the awareness of inborn errors of metabolism (IEMs), and their inheritance, symptoms, treatment modalities, and preventive measures among parents of Syrian refugee children who were admitted to our outpatient clinics.Materials and Methods: A survey using a semi-structured interview questionnaire in Arabic was conducted among randomly selected parents. Demographic data were evaluated. The relationship between demographic data, including education level and income with study variables were analyzed.Results: 123 parents participated in the study. The rate of consanguinity was 67.5%. The majority (82.9%) of participants were unaware of the term IEM. The education level of parents were shown to have an impact on the knowledge of IEM (p0.05). Nearly all participants mentioned that they wanted to be informed of the newborn screening program of Turkey.Conclusion: This is a unique study on the awareness of IEM among refugee Syrian population in Turkey. Understanding the level of awareness of CMDs of the refugee population, may improve diagnosis and management strategies, and will be a solution, at least in part, for a global problem.